Effect of C12H25O– substituent position on the self-assembly behaviour of C6H5COO–Ala–Ala dipeptide. (30th June 2021) - Lin, Shuwei; Tong, Qiyun; Jiang, Pan; Li, Baozong; Li, Yi; Yang, Yonggang
Abstract : Intramolecular hydrogen bonding and steric hindrance of side chain lead the different molecular packing of dipeptides and the morphological transformation of self-assemblies' nanostructures. Abstract : Three dipeptides based on the Ala–Ala building block with different substituent positions of the dodecyloxy group on the benzoyl residue at the N terminus were designed and synthesized ( ortho -, meta - and para -16 ). All of them were able to spontaneously self-assemble in the mixed solvent of methanol and water (6/4, v/v). However, three dipeptides underwent a distinct kinetically controlled self-assembling process. The spectroscopic study also revealed that, for ortho -16, the phenylene groups and the peptide sequence loosely packed, while meta - and para -16 stacked into well-ordered structures with the formation of parallel β-sheets through supramolecular self-assembly. Intramolecular hydrogen bonding and steric hindrance of the dodecyloxy side chain were proposed to lead to the different self-assembling behaviour of the three isomers.